2015
DOI: 10.1103/physrevc.92.055802
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the influence of thef0(975)andϕ(1020) mesons on the surface gravitational redshift of the neutron star PSR J0348+0432

Abstract: Examination of the influence of the f 0 (975) and φ(1020) mesons on the surface gravitional redshift of the neutron star PSR J0348+0432 The effect of the mesons f0(975) and φ(1020) on the surface gravitional redshift of the neutron star PSR J0348+0432 is examined in the framework of the relativistic mean field theory by choosing the suitable hyperon coupling constants. We find that compared with that without considering the mesons f0(975) and φ(1020), the value range of the radius R of the neutron star PSR J03… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this work, we study the role played by the ωρ vector interaction and its implications for the microscopic and macroscopic properties of neutron stars focusing on new results related to GW170817. In the past, other works have already pointed to the importance of such an interaction and its relation to neutron stars [45][46][47][48][49][50][51][52][53][54][55][56][57], although it was first introduced in the context of the thickness of neutron skin in Pb 208 [58]. It has been recently shown that crossed scalar terms of the kind σδ in the Lagrangian density also affect the symmetry energy slope [59].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we study the role played by the ωρ vector interaction and its implications for the microscopic and macroscopic properties of neutron stars focusing on new results related to GW170817. In the past, other works have already pointed to the importance of such an interaction and its relation to neutron stars [45][46][47][48][49][50][51][52][53][54][55][56][57], although it was first introduced in the context of the thickness of neutron skin in Pb 208 [58]. It has been recently shown that crossed scalar terms of the kind σδ in the Lagrangian density also affect the symmetry energy slope [59].…”
Section: Introductionmentioning
confidence: 99%
“…Different theoretical approaches have been used to study the properties of homogeneous nuclear matter, including ab initio (Zuo et al 2002a,b;Baldo & Maieron 2004;Dickhoff & Barbieri 2004;Bombaci et al 2005;Lee 2009;Baldo et al 2012;Carlson et al 2015) and phenomenological (Glendenning 1985;Rikovska Stone et al 2003;Stone & Reinhard 2007;Dutra et al 2012;Sellahewa & Rios 2014;Dutra et al 2014;Whittenbury et al 2014) approaches, and these studies cover large ranges of baryon number density, temperature, and isospin asymmetry. The relativistic mean field (RMF) model, one of the phenomenological models, provides an excellent tool to study the properties of infinite nuclear matter (Chin & Walecka 1974;Walecka 1974;Glendenning 1996;Shen & Ren 1999;Shen 2002;Shen et al 2011;Zhao & Jia 2012;Zhao 2014;Dutra et al 2014;Meng et al 2016;Mu et al 2017;Bhuyan et al 2017;Biswal et al 2019;Tong et al 2020). In the framework of the RMF model, the baryons are treated as point particles and interact with each other through the exchange of scalar and vector mesons (Walecka 1974;Glendenning 1985).…”
Section: Introductionmentioning
confidence: 99%